Effectiveness And Safety Of Erdosteinie In Management Of Chronic Obstructive Pulmonary Disease (COPD): A Systematic And Meta-Analysis - Yolanda, Lorensia; Gunawan, Catherine Keiko; Sumarpo, Anton; Sahamastuti, Agnes Anania Triavika; Cokro, Fonny (Jurnal Ilmu Kedokteran dan Kesehatan, 2025)
Chronic obstructive pulmonary disease (COPD) is a chronic lung disease that cause limitation in the airflow and chronic inflammation. Erdosteine has been proposed as a potential therapeutic option for COPD management, based on its antioxidant activity and anti-inflammatory properties. The purpose of this systematic review and meta-analysis is to evaluate the effectiveness and safety of erdosteine in COPD patients. Multiple databases have been involved in the literature study following PRISMA guidelines, identifying randomized controlled trials (RCTs) that compared erdosteine with placebo. A total of seven studies were included in the qualitative analysis, and nine were analyzed quantitatively. Meta-analysis results indicated that erdosteine significantly improved forced expiratory volume in one second (FEV1), reduced reactive oxygen species (ROS) and 8-isoprostan levels, and lowered interleukin-8 (IL-8) concentrations. Subgroup analyses demonstrated greater benefits in patients with moderate to severe COPD (stage II/III). Safety analysis revealed that erdosteine was generally well-tolerated, with only mild adverse effects reported. However, study limitations included high heterogeneity and potential bias in some trials. Overall, the findings suggest that erdosteine is an effective and safe adjunct therapy for COPD.